Development of an Educational Sustainability Assessment Model: Application of the Delphi Technique and Pilot Study - Chianchana, Chaiwichit (Journal of Education and e-Learning Research, 2022)
The objective of this research was to develop an educational sustainability assessment model using the Delphi technique. The research participants were an expert panel and stakeholders of educational projects. The research instruments consisted of an open-ended questionnaire and assessment forms. The frequencies, medians, quartile deviations, means and standard deviations of the data were analysed. The research results found that the assessment framework for educational sustainability in the first round consisted of the following indicators: pre-conduct, process conduct, post-conduct and the criteria consisted of the possible opportunities in sustainability (for pre-conduct and process conduct) and true sustainability (for post-conduct). The second round of assessment indicators and criteria were high, and in the third round they were very high. A pilot study of the feasibility of sustainability (pre-conduct) found that this project had the opportunity to achieve sustainability at the highest level and all model assessment standards were at the highest level.